PENGARUH PENDIDIKAN DAN KESEMPATAN KERJA TERHADAP PERTUMBUHAN EKONOMI DI INDONESIA - Abidin, Maulana; Addainuri, Muhammad Isbad; Suci, Lestari Etika (Fakultas Ekonomi dan Bisnis Universitas Lampung, 2023)
Development is a multidimensional process or approach that involves various perspectives, including fundamental changes to social structures, community attitudes, and national institutions. In addition to continuing to accelerate economic growth, it also addresses income inequality and eradicates poverty. The method used is quantitative with the Ordinary Least Square (OLS) approach. The data utilized is Panel data from the Central Statistics Agency (BPS) source for the year 2021. The research focuses on 5 provinces: South Sumatra, West Sumatra, Jambi, Lampung, and Bengkulu. Data testing is conducted using the Common Effect Model, Fixed Effect Model, and Random Effect Model. The results indicate that through the T-test, X1 (Education: Elementary, Junior High, and High School) does not have a significant influence on economic growth, whereas X2 (Labor Force) significantly affects economic growth. The F-test results show that independent variables X1 and X2 have an impact on economic growth.